Body assembly process improvement for automotive industry - Mohd Najmi, Mohamad (2008)
An automotive body assembly system consists of many individual sub- assemblies and sheet metal parts welded. The objective in this project is to identify the problem that always happens in line assembly. Then improve the problem in line assembly to overcome from the problem arise. Hence make a comparison and find a solution about body assembly to improve the problem from the data analysis. At body assembly process there are several problem could happen such as miss the spot part, dent or hump, scratch, spatter burr and hole to the body during assembly. But the major problem happen at line assembly is spot weld and men mistake. By using 4M method which includes machine, method, material and man, this problem can be identify easily and effected. As a result there are some problem that contributes to the problem happen such as logistic problem which involve the wrong part delivery and wrong shipment. Besides that, man power and workability also be the problem to the line assembly. Lack of discipline, behaviour and competency of worker give a worse impact to the company. Wrong workability involves many of tools, machine and man power and affected the production and flow in line assembly. Spot welding becomes a problem when the current voltage supply is not enough and it can work properly. Lastly jigs and fixture need to be right servicing schedule to make sure the machine and tools are in good condition and avoid the problem happen used it. The method were used to make the analysis data is by making study case at AMM factory which more focus at body assembly line and problem occur during the process. From the data collected, analysis data can be done and improve the problem that always happen in line assembly. Hence it gives benefit to the company either in productivity or working environment from the solution has done.